The employment effects of innovations in high-tech industries - Alexander Coad; Rekha Rao (Max Planck Institute of Economics, 2007)
The issue of technological unemployment receives perennial popular attention. Although there are previous empirical investigations that have focused on the relationship between innovation and employment, the originality of our approach lies in our choice of method. We focus on four 2-digit manufacturing industries that are known for their high patenting activity. We then use Principal Components Analysis to generate a firm- and year-specific 'innovativeness' index by extracting the common variance in a firm's patenting and R&D expenditure histories. To begin with, we explore the heterogeneity of firms by using semi-parametric quantile regression. Whilst some firms may reduce employment levels after innovating, others increase employment. We then move on to a weighted least squares (WLS) analysis, which explicitly takes into account the different job-creating potential of firms of different sizes. As a result, we focus on the effect of innovation on total number of jobs, whereas previous studies have focused on the effect of innovation on firm behavior. Indeed, previous studies have typically taken the firm as the unit of analysis, implicitly weighting each firm equally according to the principle of 'one firm equals one observation'. Our results suggest that firm-level innovative activity leads to employment creation that may have been underestimated in previous studies.
Keywords: L25; O33; J01; 330; Technological Unemployment; Innovation; Firm Growth; Weighted Least Squares; Aggregation; Quantile Regression; Innovation; Hochtechnologiesektor; Beschäftigungseffekt; Technischer Fortschritt; Arbeitslosigkeit; USA